Women's mobility and transport in the peripheries of three African cities: Reflecting on early impacts of COVID-19. (September 2021) - Porter, G.; Murphy, E.; Adamu, F.; Dayil, P.B.; De Lannoy, A.; Han, S.; Mansour, H.; Dungey, C.; Ahmad, H.; Maskiti, B.; S, Clark; Van der Weidje, K.
Abstract: This paper reflects on the mobility experiences of women in African cities in COVID-19, based on research conducted both prior to and following entry into the COVID-19 'moment'. It draws on material collected during an ongoing action research study aimed at addressing the everyday transport and mobility challenges faced by young women living in poor peripheral communities of three African cities – Abuja, Cape Town and Tunis. The project has the specific objective of supporting young women's improved access to employment opportunities through trialling various mobility/transport-related skills interventions (based on prior in-depth analysis of mobility constraints). With the onset of COVID-19 some readjustments to the research focus and planned interventions became necessary. The research teams, together with an NGO partner, are now working to chart how young women's everyday experiences of mobility and transport - both as transport users and as transport sector workers - are changing as processes of lockdown and their relaxation evolve. The paper covers the period from early 2019 through to March 2021, and offers reflections regarding 'lived experiences' of mobility practice pre-pandemic, during the pandemic, and the potential longer-term mobility-related impacts for women resident in low-income neighbourhoods in a post-COVID-19 era. This leads to consideration of key policy lessons. There is potential for prioritisation of Non-Motorised Transport interventions towards a green restart that would benefit women (for instance through promoting women's cycling), and for growing women's participation as transport operators, even perhaps the usage of drones to aid women's safer pedestrian travel. But such interventions will require far greater representation of women in COVID-19 and wider transport decision-making entities than has hitherto been the case. Highlights: Mobility and transport experiences tracked prior to and after pandemic onset. Peer researchers from study communities contribute key observations. Post-pandemic Non-Motorised Transport intervention potential. Need to grow women's participation as transport operators. Women's representation in transport decision-making entities is crucial.